PATTERNS OF HEALTHCARE ACCESS AND DETERMINANTS OF MATERNAL HEALTH ISSUES AMONG WOMEN IN RURAL KARACHI, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Maternal health is a priority public health problem in Pakistan, and rural women face socioeconomic as well as structural impediments to care. One of the explanations for bad maternal outcomes is limited access to specialists and medical centers.Objective: The research objective was to recognize the determinants of maternal health issues and measure the impediments to the use of healthcare among pregnant and postpartum women residing in rural Karachi, Pakistan.Methods: A cross-sectional survey of 200 postpartum and pregnant women was conducted through purposive sampling. The information was collected using pre pre-tested structured questionnaire along with a verbal interview. The instrument gathered data on socio-demographics, health care service use, barriers to seeking health care, and maternal health practices. Data were analyzed using descriptive statistics in SPSS 25.0, with data presented as frequencies and percentages.Results: The age group 18–28 years was a strong majority of the respondents (88.5%), and a big majority had not yet achieved middle-school education (59.5%). Pregnancy care was not common; only 27.5% of women said they had received treatment. The facility used most was the clinic (61.5%), then hospital (25%), whereas 13used home-based services. The most common hindrances to access for professional treatment were transport-related problems (32.5%), affordability of treatment (29.5%), financial instability (27.5%), and apprehension regarding doctors' attitude (10.5%). Most participants had the view that more healthcare facilities were needed, and 87% called for tertiary-care hospitals and 97% for gynecologists in the rural environment. Proper laboratory reporting during pregnancy was feasible for just 9% of the sample.Conclusion: Extensive levels of barriers to utilization of maternal healthcare in rural Karachi are revealed by the study, initiated predominantly because of socioeconomic constraints, diagnostic service unavailability, and shortages. Gap filling through the strengthening of healthcare facilities, making services accessible, and patient-oriented provider behavior is needed to bridge gaps and enhance maternal health in poor neighborhoods.